A novel combination of drug therapy to protect residual hearing post cochlear implant surgery. (2nd April 2016) - Eshraghi, Adrien A.; Roell, Jonathan; Shaikh, Noah; Telischi, Fred F.; Bauer, Blake; Guardiola, Mateo; Bas, Esperanza; Van De Water, Thomas; Rivera, Ileana; Mittal, Jeenu
Abstract: Conclusions A cocktail combining NAC, Mannitol, and Dexamethasone may be used to prevent loss of residual hearing post-implantation. There is a window of opportunity to treat the cochlea before the onset of cell death in HCs.Objective Inner ear trauma caused by cochlear implant electrode insertion trauma (EIT) initiates multiple molecular mechanisms in hair cells (HCs) or support cells (SCs), resulting in initiation of programmed cell death within the damaged tissues of the cochlea, which leads to loss of residual hearing. In earlier studies L-N-acetylcysteine (L-NAC), Mannitol, and dexamethasone have been shown independently to protect the HCs loss against different types of inner ear trauma. These three molecules have different otoprotective effects. The goal of this preliminary study is to test the efficacy of a combination of these molecules to enhance the otoprotection of HCs against EIT.Methods OC explants were dissected from P-3 rats and placed in serum-free media. Explants were divided into control and experimental groups. Control group: (1) untreated controls; (2) EIT. Experimental group: (1) EIT + L-NAC (5, 2, or 1 mM); (2) EIT + Mannitol (100, 50, or 10 mM); (3) EIT + Dex (20, 10, or 5 μg/mL); (4) EIT + L-NAC + Mannitol + Dex. After EIT was caused in an in-vitro model of CI, explants were cultured in media containing L-NAC alone, Mannitol alone, or Dex alone at decreasing concentrations. Concentrations of L-NAC, Mannitol, and Dex that showed 50% protection of hair cell loss individually were used as a combination in experimental group 4.Results There was an increase of total hair cell (THC) loss in the EIT OC explants when compared with control group HC counts or the tri-therapy cochlea. This study defined the dosage of L-NAC, Mannitol, and Dex for the survival of 50% protection of hair cells in vitro . Their combination provided close to 96% protection, demonstrating an additive effect.